Mobilidade sócio-ocupacional e mobilidade espacial: diferenciações entre hierarquias urbanas para o mercado de trabalho formal, Brasil, 2000-2009 - Luzia Maria Cavalcante de Melo (2012)
Theoretical and empirical evidence suggest that individuals who migrate to regions that have more locational advantages, relative to region of origin, have greater chances of upward social and occupational mobility. Whereas different urban hierarchies reflect, among other things, local economic differences, individuals who move from a lesser hierarchy to a higher one in the urban scale would increase their chances of upward social and occupational mobility. In Brazil, the intense migratory movement of the 1950-1970 period was parallel to the phenomenon of increasing inequality between the major regions - specifically between the Northeast and Southeast - and the great increase in the rates of social mobility, especially among migrants in their destination. This thesis aims to analyze the relationship between socio-occupational mobility, spatial mobility and locational economic differences in Brazil, represented by different urban hierarchies in the period 2000-2009. For this, we used data from the Rais-migra through the period 2000-2009, so that this analysis addresses the socio-occupational mobility of individuals employed in the formal labor market. We used a three-digit classification of the CBO-2002 to calculate socio-occupational scores to establish the strata in which socio-occupational mobility was observed. The spatial mobility was observed from the displacement of individuals between urban hierarchies established in REGIC, under the hypothesis that these hierarchies reflect different economic locational conditions. To estimate the relationship between socio-occupational mobility, spatial mobility and locational differences, we used a multinomial logit model. The results show that the relative chances of upward social and occupational mobility of those who perform spatial mobility between the urban hierarchies, vis-à-vis the chances of downward social and occupational mobility is higher than for those who remain in their place of origin. With regard to differences between the hierarchies, the results show a change in the locational pattern of occupational opportunities for migrants, which also reflects a change in location of economic activities. According to the results, unlike previous decades, the ACP Sao Paulo seems to represent no more the best destination for those seeking better social and occupational conditions, especially those that originate in regions lagging behind. Evidence of this is the fact that with the exception of migrants originating from the Metropolis, for workers who have origins in other regions, to migrate to Sao Paulo represents no significant difference in their relative chances of upward occupational mobility social. Hierarchies Metropolis and Regional Capital noteworthy for being the only ones that showed positive relative chances of upward social and occupational mobility statistically significant for migrants from all regions of origin (except São Paulo). These results confirm that the economic dynamics is expanding and gaining new spaces, which means that those who leave their home regions have, currently, alternative sites in the search for higher chances of socio and occupational mobility. This also represents change in the spatial distribution of the workforce, with new spaces presenting greater economic dynamism, the trend is that migration flows no longer concentrate in São Paulo - as in previous years - but there is a better distribution, with considerable migrant flow to centers intended as a middle position in the urban hierarchy.